Correlation Analysis of Seasonal Changes on Aerosol Concentration Using Remote Sensing in Java Island - Muhammad, Garda Asa; Amaanah, Annisa; Dewi, Vanya Chathy Kemala (Proceedings of The International Conference on Data Science and Official Statistics, 2025)
Aerosols are small particles in the atmosphere that affect the climate through direct and indirect mechanisms. Aerosols can influence the climate and play a role in cloud formation and precipitation. This study aims to analyze the relationship between seasonal changes and aerosol concentrations, and to identify parameters that influence aerosol concentrations in Java Island using remote sensing. The method used in this study is the Pearson correlation test to determine the relationship between seasonal changes and aerosol concentrations in the atmosphere. The results show that there is a relationship between Aerosol Optical Depth (AOD) and rainfall with a correlation value (R) of 0.8. This result indicates a significant relationship between the two variables. Meanwhile, the analysis results between Aerosol Optical Depth (AOD) and wind speed show a correlation value (R) of 0.05. This result indicates that the relationship between Aerosol Optical Depth (AOD) and wind speed is very weak between the two variables.